A LOFAR mini-survey for low-frequency radio emission from the nearest brown dwarfs. Issue 2 (19th August 2016) - Burningham, Ben; Hardcastle, M.; Nichols, J. D.; Casewell, S. L.; Littlefair, S. P.; Stark, C.; Burleigh, M. R.; Metchev, S.; Tannock, M. E.; van Weeren, R. J.; Williams, W. L.; Wynn, G. A.
Abstract: We have conducted a mini-survey for low-frequency radio emission from some of the closest brown dwarfs to the Sun with rapid rotation rates: SIMP J013656.5+093347, WISEPC J150649.97+702736.0 and WISEPA J174124.26+255319.5. We have placed robust 3σ upper limits on the flux density in the 111–169 MHz frequency range for these targets: WISE 1506: <0.72 mJy; WISE 1741: <0.87 mJy; SIMP 0136: <0.66 mJy. At 8 h of integration per target to achieve these limits, we find that systematic and detailed study of this class of object at LOFAR frequencies will require a substantial dedication of resources.